Connectivity and flow regime direct conservation priorities for pelagophil fishes. Issue 11 (24th June 2021) - Mollenhauer, Robert; Brewer, Shannon K.; Perkin, Joshuah S.; Swedberg, Dusty; Wedgeworth, Maeghen; Steffensmeier, Zachary D.
Abstract: Dam construction threatens global aquatic biodiversity by fragmenting stream networks and altering flow regimes. The negative effects of dams are exacerbated by increased drought periods and associated water withdrawals, especially in semi‐arid regions. Stream fishes are particularly threatened owing to their mobile nature and requirement for multiple habitats to complete their life cycles. An understanding of relationships with fragmentation and flow regimes, particularly as coarse‐scale (e.g. catchment) constraints on species distributions, is essential for stream fish conservation strategies. Prairie chub ( Macrhybopsis australis ) is a small‐bodied minnow (Cyprinidae) with poorly understood ecology endemic to the North American Great Plains. Suspected declines in abundance and extirpations have resulted in conservation interest for prairie chub at state and federal levels. Prairie chub is thought to share its reproductive strategy with pelagic‐broadcast spawning minnows (pelagophils). Freshwater pelagic‐broadcast spawning fishes have been disproportionately affected by fragmentation and streamflow alteration globally. Relationships of prairie chub occurrence with coarse‐scale fragmentation and streamflow metrics were examined in the upper Red River catchment. Occurrence probability was modelled using existing survey data, while accounting for variable detection. The modelled relationships were used to project the distribution of prairie chub in both a wet and dry climatic period. The probability of prairie chub occurrence was essentially zero at sites with higher densities of upstream dams, but increased sharply with increases in flow magnitude, downstream open mainstem, and flood duration. The projected distribution of prairie chub was broader than indicated by naïve occurrence, but similar in both climatic periods. The occurrence relationships are consistent with the hypotheses of pelagic broadcast spawning and represent coarse‐scale constraints that are useful for identifying areas of the stream network with higher potential for finer‐scale prairie chub conservation and recovery efforts. In addition to informing pelagophil conservation, the relationships are also applicable to pelagic‐broadcast spawning fishes in marine environments.